The impact of globalisation on supply chains - Mangan, D. John (Henry Stewart Talks, 2010)
Understanding globalisation, growth of international trade, the importance of containerisation, extended logistics reach, measuring global logistics performance, enhancing the competitiveness of the global, sustainable supply chain
Reviewed at 2016/06/30